Kualiti Jalinan Hubungan Ketua-Subordinat dan Kepuasan Kerja - Zamani Ahmad, Mansor (2009)
Research on superior-subordinate relationship quality is still under explored phenomena in Malaysia. This superior-subordinate relationship quality is based on mutually concept is used to investigate the subordinate behavior through job satisfaction. This research is focusing on the perception of subordinate on superior-subordinate relationship quality. The purpose of the research is to investigate the relationship between the dimension of superior-subordinate relationship quality consist affect, loyalty, contribution and satisfaction to Administration and Diplomatic Officer (PTD) in Kuala Lumpur and Putrajaya. Two hypotheses are advanced;first, there is a relationship between superior-subordinate relationship quality and job satisfaction. Second, there is an effect on superior-subordinate relationship quality to the job satisfaction. 269 respondents from Administration and Diplomatic Officer (PTD) which in grade M 41 at Prime Minister Department, Public Services Department, Ministry of Home Affairs, Ministry of Transport, Ministry of Health and Ministry of Housing and Local Government are selected. Two statistical approaches were used to test the hypotheses. First is Pearson Correlations which to test the relationship between two variables and second is Multiple Regression which to test the effect on the superior-subordinate relationship quality to job satisfaction. These two analyses confirmed that there is a positive significant relationship between the dimension of superior-subordinate relationship quality and job satisfaction and confirmed that the factors in superior-subordinate relationship quality have indirect effect on job satisfaction.